Europeanisation and Hibernicisation : Ireland and Europe - McCall, Cathal, 1966-; Wilson, Thomas M., 1951- (European studies (Amsterdam, Netherlands) ;, 2010)
Scholars across the humanities and social sciences are increasingly examining the importance of European integration and Europeanisation to changing notions of local, regional, national and supranational identity in Europe. As part of this interest, anthropologists, historians, sociologists, political scientists and others have paid particular attention to the roles which EU policies and initiatives have played in the construction of local, regional and national identity in Europe, and in the reframing of various forms of culture. This volume provides the first multidisciplinary look at the impact of European integration and Europeanisation on changing culture and identity in one member state of the EU, namely Ireland (including the Republic of Ireland and Northern Ireland), and the first such look at the ways in which the cultures and identities of a member state have had an impact on various versions of 'Europe', in and outside of the EU.